The world is flat: a brief history of the twenty-first century - Friedman, Thomas L.
In The World Is Flat is Thomas L. Friedman accounts for the changes taking place in our time, as advances in technology and communications put people all over the globe in touch as never before-creating an explosion of wealth in India and China, and challenging the rest of us to run even faster just to stay in place. In The World Is Flat, Friedman articulates how and why globalization has now shifted demystifies the new flat world, as he sees it, for readers, allowing them to make sense of the scene unfolding before their eyes. According to Friedman, the flattening of the world happened at the dawn of the twenty-first century; what it means to countries, companies, communities, and individuals; how governments and societies can, and must, adapt; and why terrorists want to disrupt this process. More than ever, The World Is Flat is a reflection on one perspective of globalization, more about its ?successes? and less about its ?discontents.? According to Friedman, Globalization came in three stages. 1) Globalization 1.0: Spain ?discovering? the Americas, Great Britain colonizing India, Portugal in East Indies and East Asia; 2) Globalization 2.0: Countries no longer globalizing, and Companies begin globalizing; Finally, Globalization 3.0: Individuals begin globalizing, Broadband Internet Line, Stock Market Crash/Boom, Cost Issues, Technological Advances, and Expression. Freidman foist a model of what he sees as 10 significant moments in world economic and political history: 1) 11/9 Berlin Wall Falls, 2) Netscape (First Web Browser) goes Public, 3) Workflow ? Common Platforms, 4) Outsourcing Operations, 5) Offshore Companies, 6) Open Source Movement, 7) Supply Chain Economics, 8) Insourcing (UPS - Toshiba), 9) Self-Informing Movement (Google) , and 10) Steroids ? Talking via Internet and Wireless. In a spin that sounds less like economics and more like an exercise in rhetorical extensions of the 10 Flattening model, Friedman suggests that: 1. All ten flatteners coming together and working with each other: Southwest Airlines Online Check-In, Starbucks Coffee Combinations; 2. Horizontal Integration: Vertical ?command? structure breaking apart, Collaboration; and 3. Expansion of Playing Field: India and China ? 150 Million People More, No Legacy Infrastructure ? Cell Phones and Wireless. Finally, according to Friedman, the big can act small: Consumer becomes employee; Outsourcing saves time and money, and McDonald?s Drive-Thru Orders. Conversely, he small can act big: Technological advances in IT/Communication, Ability of internet to reach wide audience, Power of independent research, and Horizontal Collaboration.